Reprogramming of glucose metabolism in pancreatic cancer: mechanisms, implications, and therapeutic perspectives - Zhang, Yan; Li, Wancheng; Niu, Jubao; Fan, Zeyang; Li, Xin; Zhang, Hui (Frontiers in Immunology, 2025)
As a typical pathological feature of pancreatic ductal adenocarcinoma, reprogramming of glucose metabolism synergistically drives the tumorigenesis and development process through molecular mechanisms such as regulating the expression of driver genes, modifying key functional proteins, triggering mitochondrial metabolism abnormality, and remodeling the tumor microenvironment. It is worth noting that this metabolic remodeling phenomenon is significantly associated with the formation of chemoresistance. Based on the latest research progress, this paper systematically describes the molecular basis of glucose metabolic reprogramming in pancreatic cancer, drug resistance characteristics and its targeted intervention strategies, and provides a theoretical framework for the research and development of innovative drugs.